Physical and sensorial quality of Litopenaeus vannamei shrimp cultivated in freshwater (Revista de Ciências Agroveterinárias, 2018)
This experiment aimed to evaluate the quality of the marine shrimp L. vannamei farmed in fresh and salt water, with emphasis on physical and sensory parameters. For the physical parameters pH determinations were performed, water holding capacity (WHC), weight loss during cooking (PPS), texture and color (all in triplicate). For sensory analysis participated in the test 30 tasters, of both sexes, aged between 23-49 years were used to assess the shrimp according to the attributes of taste, odor, color, texture and juiciness and overall preference of appearance. Regarding the pH there was no significant difference (p>0.05) between the two treatments, as well as CRA and PPC. The color parameters (a *, b * and L *) showed uniformity in the results for both the shrimp in nature as for the cooked, with no significant differences. The texture is highlighted where there was a significant difference (p
Keywords: salinity; fresh water; astacoidea; artemia; saline waters